2019
DOI: 10.1101/689505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functionally Distinct Subgroups of Oligodendrocyte Precursor Cells Integrate Neural Activity and Execute Myelin Formation

Abstract: Recent reports revealed heterogeneity of oligodendrocyte precursor cells (OPCs). It remains unclear if heterogeneity reflects different types of cells with distinct functions, or rather transiently acquired states of cells with the same function. By integrating lineage formation of individual OPC clones, single-cell transcriptomics, calcium imaging and manipulation of neural activity, we show that OPCs in the zebrafish spinal cord can be divided into two functionally distinct entities. One subgroup forms elabo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Depending upon the OPC developmental stage, calcium fluctuations in the soma and in the processes are different, declining in OPC processes and becoming even smaller in the soma throughout development ( Krasnow et al, 2018 ). A recent interesting study has teased this out on a single cell level, combining Ca2+ imaging with single cell RNA-Seq and analyses of proliferation and differentiation in a zebrafish model where cell tracking at this granularity is possible ( Hoche et al, 2020 ). Investigators found that some calcium transients spread from processes to the cell body and were synchronized in neighboring OPCs, consistent with a small local network of connected OPCs.…”
Section: Voltage-gated Channels and Their Role In Oligodendrocyte Precursor Cell Development And Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending upon the OPC developmental stage, calcium fluctuations in the soma and in the processes are different, declining in OPC processes and becoming even smaller in the soma throughout development ( Krasnow et al, 2018 ). A recent interesting study has teased this out on a single cell level, combining Ca2+ imaging with single cell RNA-Seq and analyses of proliferation and differentiation in a zebrafish model where cell tracking at this granularity is possible ( Hoche et al, 2020 ). Investigators found that some calcium transients spread from processes to the cell body and were synchronized in neighboring OPCs, consistent with a small local network of connected OPCs.…”
Section: Voltage-gated Channels and Their Role In Oligodendrocyte Precursor Cell Development And Maturationmentioning
confidence: 99%
“…Investigators found that some calcium transients spread from processes to the cell body and were synchronized in neighboring OPCs, consistent with a small local network of connected OPCs. The location of the OPC soma mattered: OPCs that resided in axon-rich areas, vs. neuronal soma-rich areas in the spinal cord had a higher probability of exhibiting Ca2+ transients ( Hoche et al, 2020 ), indicating that there is heterogeneity and local differences in Ca2+ mediated signaling that may not be captured when sampling larger brain regions or circuits. An exciting new study sheds light on the role of these Ca2+ transients in myelin sheath regulation: they used in vivo one-photon Ca2+ imaging and found that the Ca2+ transients at myelin domains were independent of neuronal activity, and instead were due to mitochondrial release of Ca2+ in axonal and paranodal myelin itself, suggesting that myelin remodeling is independent of neuronal activity ( Battefeld et al, 2019 ).…”
Section: Voltage-gated Channels and Their Role In Oligodendrocyte Precursor Cell Development And Maturationmentioning
confidence: 99%
“…Interestingly, of 12 distinct cell subpopulations belonging to the oligodendrocyte lineage, GPR17 expression was detected only in three clusters defined as "differentiation committed precursors" (Marques et al, 2016). Moreover, a detailed spatial and functional analysis of OPC diversity, in zebrafish spinal cord, revealed that GPR17 expression is strictly present in cells localized in an axon-enriched environment and potentially able to myelinate axons, while it is virtually absent in OPCs housed in proximity of See Published version at http://dx.doi.org/10.1002/glia.23807 6 neuronal somas, that never differentiate but seem to be more involved in network formation and synaptic activity (Hoche et al, 2019).…”
Section: Gpr17 Involvement In Oligodendrogenesis and Myelinationmentioning
confidence: 99%
“…Neuronal activity can modulate oligodendrocyte progenitor cells (OPCs) proliferation, maintenance and differentiation in zebrafish and mammals (Hill et al, 2014;Zonouzi et al, 2015;Hamilton et al, 2017;Hoche et al, 2019). Glutamatergic and GABAergic neurons have been shown to form bona fide synapses on OPCs in rodents (Bergles et al, 2000;Lin and Bergles, 2004) and humans (Gallo et al, 2008), with neuronal inputs on OPCs being consistent between brain regions (Mount et al, 2019).…”
Section: The Oligodendroglial Lineage Can Perceive the Neuronal Activitymentioning
confidence: 99%
“…Although the involvement of neuron-OPCs synapses has been largely documented, non-synaptic junctions between neurons and OPCs have also been involved in the facilitation of OPCs differentiation in vitro (Wake et al, 2015; Figure 1). The control of OPCs proliferation and differentiation has been showed to depend on Ca 2+ signals triggered by neuronal activity in vitro in rodents (Wake et al, 2011) and in vivo in zebrafish (Hoche et al, 2019). However, depending on the developmental stage and the anatomical area studied, OPCs respond differently to neuronal activity, possibly related to their heterogeneous expression of voltage-gated channels and receptors to neurotransmitters (Káradóttir et al, 2008;Hoche et al, 2019;Spitzer et al, 2019).…”
Section: The Oligodendroglial Lineage Can Perceive the Neuronal Activitymentioning
confidence: 99%